2006
DOI: 10.1354/vp.43-5-689
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic/Macrophagic Pneumonitis after Intrabronchial Deposition of Vascular Endothelial Growth Factor in Neonatal Lambs

Abstract: Abstract. Preterm and young neonates are prone to inadequate surfactant production and are susceptible to respiratory distress syndrome characterized by alveolar damage and hyaline-membrane formation. Glucocorticoid therapy is commonly used in preterm and young infants to enhance lung maturation and surfactant synthesis. Recently, vascular endothelial growth factor (VEGF) was suggested to be a novel therapeutic agent for lung maturation that lacked adverse effects in mice. The purpose of this study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This subtle (not detected clinically) vascular leakage could allow extravasation of antibodies or other innate immune components (e.g., mannose-binding protein) for antigen-antibody complex formation; an important source of pyrogenicity in viral infection (19). A second potential mechanism is related to the recruitment of monocytes and macrophages to sites of VEGF expression/administration (3,27). Monocytes/macrophages are important producers of pyrogenic cytokines after phagocytosis of antigen (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This subtle (not detected clinically) vascular leakage could allow extravasation of antibodies or other innate immune components (e.g., mannose-binding protein) for antigen-antibody complex formation; an important source of pyrogenicity in viral infection (19). A second potential mechanism is related to the recruitment of monocytes and macrophages to sites of VEGF expression/administration (3,27). Monocytes/macrophages are important producers of pyrogenic cytokines after phagocytosis of antigen (38).…”
Section: Discussionmentioning
confidence: 99%
“…In a sheep model, intrabronchial deposition of exogenous rhVEGF induced a dose-dependent recruitment of monocyte/macrophages into the lung, causing gross and microscopic lesions (27). Although safety concerns regarding VEGF therapy are legitimate, studies of short-term and lower dose applications thus far have reported minimal clinical complications (8,27).…”
Section: Introductionmentioning
confidence: 99%
“…The lambs in this study were the same animals used previously to characterize the bronchoscopic deposition of VEGF in the lungs of neonatal lambs [25]. The study was conducted in full-term lambs that did not have RDS.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in full-term lambs that did not have RDS. Briefly, healthy male and female neonatal lambs at 2–4 days of age (see [25]) were randomly assigned to three groups: a saline-inoculated group ( n = 3), a VEGF-inoculated group (for low dose VEGF n = 1 at all time points; for medium dose VEGF n = 2 for 16 h, n = 3 for 24 h, n = 2 for 32 h; for high dose VEGF, n = 1 for all time points), and a bovine serum albumin (BSA)-inoculated group ( n = 2). Lambs were sedated with xylazine (0.1 mg/kg) intravenously (i.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation